Health reform and malaria control in two endemic areas of Colombia, 1982-2004. (Colombia Medica, 2007)
Introduction: During the last years Colombian health policy has experienced deep  changes whose effects on public health are controversial. Objectives: Case study carried out in two municipalities in order to describe the changes in malaria control program and its relationship with Colombian health reforms. Methodology: The municipalities of Zaragoza and Tarazá were selected because they present high rates of   malaria incidence in the department (state) of Antioquia, Colombia. The study combined qualitative and quantitative techniques to obtain and to process the information. The official files of the program were analyzed for the period 1982-2004. Key informants, selected by their experience with malaria and its control programs, were interviewed. Results: In connection with the policy for malaria control, three moments were identified: the vertical program  under Ministry of Health (1975-1982) responsability; the departmental program (19831990); and the organization of the program according to the regulated competition model (1991-2004). During the second moment improvement in the control activities accompanied by a reduction of the mortality were observed. Since 1991, a deterioration in the control of malaria, associated  to the decentralization and the subjection of the sanitary politics to the principles of the market, was noted; this deterioration is characterized by the progressive lost of force of the responsibility of the State on malaria control, the loss of the installed capacity and the Know-How, the fragmentation of control actions, the collapse of information systems and the deterioration of mortality and morbidity indicators. Conclusions:  Both observed cases suggest a detriment in the efficiency, effectiveness and quality of malaria control actions, associated with health reforms implemented in Colombia since 90s, which could also be  present in other municipalities of the country.